Clinical Review of Smartphone Applications in Parkinson's Disease. Issue 4 (20th July 2022) - Tripathi, Susmit; Malhotra, Ashwin; Qazi, Murtaza; Chou, Jingyuan; Wang, Fei; Barkan, Samantha; Hellmers, Natalie; Henchcliffe, Claire; Sarva, Harini
Abstract : Background: Parkinson's disease (PD) is the second leading neurodegenerative disease worldwide. Important advances in monitoring and treatment have been made in recent years. This article reviews literature on utility of smartphone applications in monitoring PD symptoms that may ultimately facilitate improved patient care, and on movement modulation as a potential therapeutic. Review Summary: Novel mobile phone applications can provide one-time and/or continuous data to monitor PD motor symptoms in person or remotely, that may support precise therapeutic adjustments and management decisions. Apps have also been developed for medication management and treatment. Conclusions: Smartphone applications provide a wide array of platforms allowing for meaningful short-term and long-term data collection and are also being tested for intervention. However, the variability of the applications and the need to translate complicated sensor data may hinder immediate clinical applicability. Future studies should involve stake-holders early in the design process to promote usability and streamline the interface between patients, clinicians, and PD apps.